Meaningful Participation Through Online Channels in Legislation Making in Indonesia via dpr.go.id Page - Soeprapto, R. Wahjoe Poernomo (Faculty of Law Universitas Trunojoyo Madura, 2024)
Public participation in the legislative process is essential in any democratic nation. Transparency and openness are vital for state administrators to facilitate community involvement in shaping government policies. The regulatory framework for community participation is established in Law No. 13 of 2022 as a direct consequence of Constitutional Court Decision No. 91/PUU-XVIII/2020, using the term